+0  
 
0
244
1
avatar

If we express \(x^2 + 4x + 5\) in the form \(a(x - h)^2 + k\), then what is h?

 Dec 29, 2017

Best Answer 

 #1
avatar+7350 
+1

x2 + 4x + 5

                                         Add and subtract  (4/2)2  ,  which is  4  , to the expression.

=  x2 + 4x + 4 + 5 - 4

                                         Now factor the first three terms as a perfect square trinomial.

=  (x + 2)2 + 5 - 4

 

=  1(x - -2)2 + 1

 

So  a = 1 ,  h = -2  ,  and  k = 1 .

 Dec 29, 2017
 #1
avatar+7350 
+1
Best Answer

x2 + 4x + 5

                                         Add and subtract  (4/2)2  ,  which is  4  , to the expression.

=  x2 + 4x + 4 + 5 - 4

                                         Now factor the first three terms as a perfect square trinomial.

=  (x + 2)2 + 5 - 4

 

=  1(x - -2)2 + 1

 

So  a = 1 ,  h = -2  ,  and  k = 1 .

hectictar Dec 29, 2017

23 Online Users

avatar
avatar
avatar